(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
Food price volatility threatens economic stability and consumer welfare in emerging economies. While government interventions are widely studied, the role of marketing instruments in stabilizing domestic food markets remains underexplored. This study examines how price differentiation, supply chain coordination, and retail integration influence food price fluctuations. Using panel data and econometric analysis, the findings show that stronger marketing integration reduces price volatility by improving information flow and moderating demand–supply shocks. The results reposition marketing as a structural stabilization mechanism and provide policy-relevant insights for sustainable food market management.